Faktor-Faktor yang Mempengaruhi Perilaku Merokok pada Siswa SMKN 3 Kota Jambi Tahun 2025 - Wahyu Nurjayanti; M. Ridwan; Kasyani Kasyani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Jambi Province has the highest prevalence of tobacco smoking among individuals aged 15 years and above in Indonesia within the past month. In addition, Jambi also records the highest average number of cigarettes smoked per day by individuals in this age group, with an average of 18 cigarettes per day. This situation highlights the significant level of tobacco consumption in the province, which may affect adolescent smoking behavior, including among vocational school students. Objective: To analyze the factors influencing smoking behavior among students of SMKN 3 Kota Jambi.  This study was a quantitative research with a cross-sectional design. The sample consisted of 114 students selected using random sampling techniques. The study was conducted at SMKN 3 Kota Jambi. The dependent variable was smoking behavior, while the independent variables included knowledge, parental influence, peer influence, and exposure to cigarette advertisements. Data were analyzed using univariate and bivariate analyses with the chi-square test at a 95% confidence interval. The proportion of students who smoked at SMKN 3 Kota Jambi in 2025 was 46.5%. There were significant associations between smoking behavior and knowledge (p-value = 0.008; PR: 1.730; 95% CI: 1.163–2.573), parental influence (p-value = 0.023; PR: 1.597; 95% CI: 1.081–2.357), and peer influence (p-value = 0.001; PR: 2.038; 95% CI: 1.346–3.086). However, no significant association was found between exposure to cigarette advertisements and smoking behavior (p-value = 0.127; PR: 1.366; 95% CI: 0.929–2.010).The factors influencing smoking behavior among students of SMKN 3 Kota Jambi were knowledge, parental influence, and peer influence.